The global economy and the euro area: Expansion continues but Is losing momentum - Ferdinand Fichtner; Guido Baldi; Geraldine Dany-Knedlik; Hella Engerer; Stefan Gebauer; Malte Rieth (DIW Weekly Report, 2018)
The global economy is likely to grow by over four percent this year and somewhat less next year. DIW Berlin has slightly raised its forecast for both years. Developed economies as well as emerging markets are experiencing an upturn; however, growth rates are likely to be slightly lower in the future. One reason for the sound global economy is the fact that the labor market situation is steadily improving, leading to an increase in private consumption. Along with fiscal stimuli in the form of tax cuts and government spending programs, more private consumption is also likely to trigger corporate investment activities. Monetary policy remains expansionary, but gradual increases in interest rates in major economies as well as the European Central Bank's (ECB) phasing-out of government bond purchases may somewhat curb growth in the U.S. and the euro area. This would also weaken the expansion in emerging economies. Risks to global growth stem from protectionist activities in the United States as well as political uncertainty in Europe.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook